Perkembangan masyarakat akibat pertumbuhan industri di daerah Nusa Tenggara Barat penulis, Jacub Ali, Kisman Pangeran, Syamsidar ; editor, H.R.J. Siregar, Suratmin - ALI, Yacub; Pangeran, Kisman; Syamsidan; Siregar, H.R.J; Suratmin (1990)
xiii, 81 hlm ilus 23 cm